Optical diagnostics of radio-frequency plasmas containing CHF3 and CHF3/O-2: Laser-induced fluorescence of CF2, CF, and O atoms, and optical emission from H, F, and O - Hancock, G; Sucksmith, J (2002)
The effect of the addition of O2 to the plasma was studied, both by observations of the reduction of fluorocarbon radical concentrations, and by measurements of group-state O atoms by two-photon excitation and subsequent fluorescence. It was shown that actinometry of O atoms is an unreliable indicator of the relative concentration of the ground-state species.